METHODOLOGY FOR RELIABILITY ASSESSMENT OF RELAY PROTECTION AND AUTOMATION DEVICES - Fedoriv, Mykhaylo; Kurlyak, Petro; Hlad, Ivan; Batsala, Yaroslav; Viznovich, Vitalij; Yatskivky, Andrij (SWorld-Ger Conference proceedings, 2025)
Based on the obtained statistical data, an analysis of the reliability of relay protection devices and automation of power supply systems was conducted. It was shown that the need to take into account their reliability when assessing the reliability of el